The impact of immigration on occupational wages: Evidence from Britain - Stephen Nickell; Jumana Saleheen (Federal Reserve Bank of Boston, 2008)
This paper asks whether immigration to Britain has had any impact on average wages. There seems to be a broad consensus among academics that the share of immigrants in the workforce has little or no effect on the pay rates of the indigenous population. But the studies in the literature have typically not refined their analysis by breaking it down into different occupational groups. In this paper we find that once the occupational breakdown is incorporated into a regional analysis of immigration in Britain, the immigrant-native ratio has a significant, small, negative impact on average wages. Closer examination reveals that the biggest impact is in the semi/unskilled services sector. This finding accords well with intuition and anecdote, but does not seem to have been recorded previously in the empirical literature.
Keywords: J6; 330; immigration; occupation; wages